Computational Intelligences in the post-Environmental Design. Examples from MAILB - Giuseppe Ridolfi; Arman Saberi (Agathón)
The article addresses the environmental question by critiquing the anthropocentric vision, still alive in the design debate and practice, as a remnant of the underlying dualism humanity/environment. It opposes the co-evolutionist and New Realism theses re-elaborated in the light of a new metalanguage (Digital Mathema) capable of ‘giving voice’ to the multitude of agents and to activate forms of collaborative intelligence (Computational Intelligences), enabling design explorations beyond established norms and the already known. Following is a description of Parametric and Generative Design and the Mailab research laboratory’s experiences. The conclusion is an invitation to reflect on the possible side effects that could arise from digital marking and from an excessive emphasis on the ‘know-how’.